Self-diffusion of mo lecules in water-ethanol solutions of low concentration. Neutron data - Vasylkevych, O.A.; Slisenko, V.I. (Доповіді НАН України, 2019)
The work is devoted to the abnormal behavior of dilute water-alcohol solutions. The dynamics of molecules of the water-ethanol system, depending on the concentration at 281 K, is researched by the method of quasi-elastic scattering of slow neutrons. The total self-diffusion coefficient of molecules D, its single-particle Ds₋p and collective Dcoll components, and the time of settled molecule’s life in the oscillating state τ₀ are determined. The region of small concentrations was studied in detail, and two minima in the coefficients D and Ds₋p were detected in the vicinity of concentrations X = 0.04 mol.f. and X = 0.2 mol.f. Time τ₀ at these concentrations is increasing significantly. This indicates a significant decrease in the intensity of the activation mechanism of diffusion of molecules, which is quite possible due to the binding of water and ethanol molecules into complexes (clusters).